Liver fat and lipid oxidation in humans. - Kotronen, A; Seppälä-Lindroos, A; Vehkavaara, S; Bergholm, R; Frayn, K; Fielding, B; Yki-Järvinen, H (2009)
BACKGROUND: Studies in animals show that changes in hepatic fatty acid oxidation alter liver fat content. Human data regarding whole-body and hepatic lipid oxidation are controversial and based on studies of only a few subjects. AIMS: We examined whether whole-body and hepatic lipid oxidation are altered in subjects with non-alcoholic fatty liver disease (NAFLD) compared with controls. METHODS: In vivo measurements of rates of substrate oxidation and insulin sensitivity (using the euglycaemic hyperinsulinaemic clamp technique in combination with indirect calorimetry and infusion of [3-(3)H]glucose) were performed in subjects with NAFLD [mean liver fat 14.0% (interquartile range 7.5-20.5%), n=29] and in control subjects [1.6% (1.0-3.0%), n=29]. Liver fat was measured using proton magnetic resonance spectroscopy. Plasma concentrations of 3-hydroxybutyrate (3-OHB) were measured as markers of hepatic lipid oxidation. RESULTS: In the basal state, substrate oxidation rates and serum 3-OHB concentrations were comparable in subjects with and without NAFLD. Plasma 3-OHB concentrations were similarly suppressed by insulin in both the groups. During the insulin infusion, whole-body lipid oxidation was inversely correlated with insulin-stimulated glucose disposal (r=-0.48, P<0.0001), which was lower in subjects with NAFLD [3.7+/-0.2 mg/(kg fat-free mass min)] than in the control subjects [5.0+/-0.3 mg/(kg fat-free mass min), P=0.0008]. CONCLUSIONS: Hepatic lipid oxidation is unchanged in NAFLD. Whole-body lipid oxidation is increased because of peripheral insulin resistance. These data imply that alterations in hepatic fatty acid oxidation do not contribute to liver fat content in humans.